APLIKASI SISTEM PAKAR MENDETEKSI KERUSAKAN PADA MESIN TOYOTA 4A-FE BERBASIS WEB - Hendi; Fajrin, Alfannisa (Computer Science and Industrial Engineering, 2022)
Bengkel Sinar Jaya is an individual-owned business engaged in services, namely selling car spare parts and repairing cars that have problems. In its business activities, it still uses a manual system and has not used a computer system, except managing data on expenses, income, and processing of financial reports at the Sinar Jaya workshop. To make the workshop more advanced and modern, the author wants to try to make an Expert System application for Detecting Damage to the Toyota 4A-FE Engine Web-Based to make it easier for our customers to find out the damage that is happening to their car engine and recommend our workshop shop to become a place to repair customers' cars using expert system applications. Customers can also search for the car spare parts they need to repair the car at the Sinar Jaya workshop, in the application there are also instructions for detecting damage to the customer's car and components that are damaged in the Toyota 4A-FE engine by selecting one of the problems that occur. on the customer's car so that the application can detect the damage experienced by the customer's car. Customers can also find solutions and Instructions for components that need to be replaced or repaired.